Pulp protectors: The search for effectiveness in dental treatment (Research, Society and Development, 2024)
In this bibliographic review, the pulp protectors used in dental treatments are analyzed to identify the most appropriate one. Pulp capping is necessary after removing tissue affected by caries or trauma, in order to preserve pulp vitality and prevent tooth sensitivity. It is essential that dentists know the types of coatings and properties of pulp dentine protectors, as well as their interaction with the pulp, to perform the treatment optimally. In addition, a good clinical diagnosis must be made and contraindications considered before performing pulp capping. It is not recommended in cases of aged pulp, irreversible pathology or large hemorrhage. The objective of this study is to compare the characteristics of the most commonly used pulp protectors today and determine which is the most effective for dental treatments. It is concluded that Biodentine is the most suitable pulp protector due to its biocompatibility, ease of handling and ability to stimulate the formation of reparative dentin.